Next-generation care pathways for allergic rhinitis and asthma multimorbidity: a model for multimorbid non-communicable diseases-Meeting Report (Part 1) - Bousquet, Jean (2020)
In all societies, the burden and cost of allergic and chronic respiratory diseases are increasing rapidly. Most economies are struggling to deliver modern health care effectively. There is a need to support the transformation of the health care system for integrated care with organizational health literacy. MASK (Mobile Airways Sentinel NetworK) (1), a new development of the ARIA (Allergic Rhinitis and its Impact on Asthma) initiative, and POLLAR (Impact of Air POLLution on Asthma and Rhinitis, EIT Health) (2), in collaboration with professional and patient organizations in the field of allergy and airway diseases, are proposing reallife integrated care pathways (ICPs) (3)-centred around the patient with rhinitis and using mHealth monitoring of environmental exposure (4). An expert meeting took place at the Pasteur Institute in Paris, December 3, 2018. The aim was to discuss nextgeneration care pathways: (I) Patient participation, health literacy and self-care through technology-assisted “patient activation”; (II) Implementation of care pathways by pharmacists and (III) Next-generation guidelines assessing the recommendations of GRADE guidelines in rhinitis and asthma using real-world evidence (RWE) assessed by mobile technology. The EU (5) and global political agendas are of great importance in supporting health care transformation. MASK has been recognized by DG Santé as a Good Practice (6) in the field of digitally-enabled, integrated, person-centred care. The one-day meeting objectives were clear (Figure 1). The meeting was followed by a workshop. The present paper reports the background of the two-day meeting. [...]